Counterexample to the Generalized Bogomolov–Gieseker Inequality for Threefolds. (14th June 2016) - Schmidt, Benjamin
Abstract: We give a counterexample to the generalized Bogomolov–Gieseker inequality for threefolds conjectured by Bayer, Macrì, and Toda using the blow up of a point in three-dimensional projective space.